Ethics and Literary Practice II: Refugees and Representation (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
A companion volume to Ethics and Literary Practice I (MDPI 2020), this book collects thirteen original essays under the governing rubric, “Refugees and Representation.” Drawing on theoretical frameworks and displaying a repertoire of performative practices,the essays across the disciplinary fields political theory, philosophy, literary and cultural studies, and history, explore the layered nature of the often-intractable questions accompanying the right to asylum. Faced with the sadly quotidian headlines of despair and the rhetorical impasse they so often generate, the contributors assembled here project alternate horizons and outward passages that may illuminate the condition of forced migrants and refugees. Among the themes addressed by to the essays are: an understanding of the history and practice of asylum from antiquity to the present day; how writers across a range of genres deal with issues of representing the struggles of refugee experience; what possibilities open up for more just global responses to the suffering of refugees; and what literary texts and their interpretive practice can bring to an ethical-politics devoted to the question of the refugee.